Chemistry, chemoecology, and bioactivity of the South China Sea opisthobranch molluscs and their dietary organisms - Wang, Jian-Rong; He, Wen-Fei; Guo, Yue-Wei (Journal of asian natural products research, 2013)
Opisthobranchs are slow-moving, brightly colored, and shell-less slug. Interestingly, these naked molluscs appear to be free of predation causing great interests to biologists, chemists, and pharmacologists as well. It is well documented that their ability to escape predation is realized by utilizing chemical substances as defensive allomones. Due to their extraordinary capacity to produce a variety of chemical defensive molecules and in particular, some of which exhibited promising pharmacological activities, opisthobranch molluscs became the hotspot of research subject in the recent years. The authors and co-workers have systematically investigated the possible diet relationship between the South China Sea opisthobranch molluscs and their related prey organisms, including sponges, corals, and algae in the last decade. A series of interesting results have been obtained concerning the chemistry and chemoecology of the studied marine organisms. The present review focuses on recent development dealing with chemistry, chemoecology, and bioactivity of the South China Sea opisthobranch molluscs and their dietary organisms. Some selected representative examples are described in detail.